Phosphoinositide 3-kinase-δ regulates fungus-induced allergic lung inflammation through endoplasmic reticulum stress. Issue 1 (5th November 2015) - Lee, Kyung Sun; Jeong, Jae Seok; Kim, So Ri; Cho, Seong Ho; Kolliputi, Narasaiah; Ko, Yun Hee; Lee, Kyung Bae; Park, Suk Chul; Park, Hae Jin; Lee, Yong Chul
Abstract : Background: Sensitisation with Aspergillus fumigatus ( Af ) is known to be associated with severe allergic lung inflammation, but the mechanism remains to be clarified. Phosphoinositide 3-kinase (PI3K)-δ and endoplasmic reticulum (ER) stress are suggested to be involved in steroid-resistant lung inflammation. We aimed to elucidate the role of PI3K-δ and its relationship with ER stress in fungus-induced allergic lung inflammation. Methods: Using Af -exposed in vivo and in vitro experimental systems, we examined whether PI3K-δ regulates ER stress, thereby contributing to steroid resistance in fungus-induced allergic lung inflammation. Moreover, we checked expression of an ER stress marker in lung tissues isolated from patients with allergic bronchopulmonary aspergillosis. Results: Af -exposed mice showed that ER stress markers, unfolded protein response (UPR)-related proteins, phosphorylated Akt, generation of mitochondrial reactive oxygen species (mtROS), eosinophilic allergic inflammation, and airway hyperresponsiveness (AHR) were increased in the lung. Similarly, glucose-regulated protein 78 was increased in lung tissues of patients with ABPA. A PI3K-δ inhibitor reduced Af -induced increases in ER stress markers, UPR-related proteins, allergic inflammation and AHR in mice. However, dexamethasone failed to reduce Af -induced allergic inflammation, AHR and elevation of ER stress. Administration of an ER stress inhibitor or a mtROS scavenger improved Af -induced allergic inflammation. The PI3K-δ inhibitor reduced Af -induced mtROS generation and the mtROS scavenger ameliorated ER stress. In primary cultured tracheal epithelial cells, Af -induced ER stress was inhibited by blockade of PI3K-δ. Conclusions: These findings suggest that PI3K-δ regulates Af -induced steroid-resistant eosinophilic allergic lung inflammation through ER stress.